Estimation of Stature From Facial Dimensions. A CrossSectional Study Among Nepalese Medical Students in Eastern Nepal - Timsinha, Sidarth; Pokharel, Dikshanta; Kumar Shah, Rajesh; Bahadur Parajuli, Surya; Ahmed Khan, Sajjad (Birat Journal of Health Sciences, 2023)
Introduction: Estimation of stature or height is critical in forensic and medicolegal examinations, for establishing the identity of a living or dead individual. Since craniofacial structures are mostly made of hard tissue that is generally indestructible, careful examination of these can provide a good estimate of the stature of an individual. Objective: To estimate stature from morphological facial height and bizygomatic breadth of the face and to develop regression formulas for estimating stature based on two facial measurements among Nepalese medical students. Methodology: This prospective cross-sectional study was conducted from December 2022 to June 2023, in the Department of Forensic Medicine at Birat Medical College and Teaching Hospital after obtaining ethical clearance from the Institutional Review Committee (IRC). A total of 216 preclinical Nepalese medical students were included in the study, comprising 107 males and 109 females aged 18 to 26 years. Stature and two facial measurements i.e., morphological facial height and bizygomatic facial breadth were measured on each participant following standard methods and techniques. Karl Pearson’s correlation coefficient and linear regression were used to estimate stature. Results: The average height of males and females was 170.70(±5.59) cm and 156.92(±5.58) cm respectively. The stature and facial measurements of males were significantly higher than females (p < 0.05). Morphological facial height showed a better correlation of stature with a higher “r” value of 0.297 in males and 0.268 in females than Bizygomatic breadth with a lesser “r” value of 0.278 in males and 0.214 in females. Conclusion: The correlation coefficient (r) between stature and morphological facial height and bizygomatic facial breadth measurements was less than 0.5. This implies that the estimation of stature is less reliable with the help of these facial measurements. These facial measurements can be used in the absence of other better parameters such as long bones or when simply facial remains are brought in for forensic examination.